Covid‐19 laryngectomized patients care, on field experience, and considerations. Issue 4 (21st February 2021) - Ricciardiello, Filippo; Caraglia, Michele; Romano, Gian Marco; Longo, Giuseppe; Russo, Giuseppe; Mazzone, Salvatore; Accardo, Nunzio; Abate, Teresa; Oliva, Flavia; Motta, Giovanni; Bocchetti, Marco
Abstract: Laryngectomized patients showed an unconventional response to SARS‐CoV‐2 viral infection. Here, we describe five different patient cases along with our interpretation of the phenomena and suggestions for their safe management. Abstract : Laryngectomized patients showed an unconventional response to SARS‐CoV‐2 viral infection. Here, we describe five different patient cases along with our interpretation of the phenomena and suggestions for their safe management.